Analysis of coffee production efficiency and productivity strategy in African and non‐African countries. Issue 4 (28th July 2022) - Yang, Chih‐Yu; Lu, Ching‐Cheng; Chiu, Yung‐Ho; Lin, Tai‐Yu
Abstract: This study used 39 coffee producing countries (CPC) in African and non‐African countries as the research object to evaluate the coffee production efficiency and coffee productivity of CPC from 2013 to 2017. Empirical results show that during the study period, among 14 countries with coffee production efficiency greater than 1, Lao (1.7265), Viet Nam (1.4282), and Indonesia (1.3113) are located in Asia, and Ghana (1.3741) and Ethiopia (1.1357) are African countries, the rest of the countries are distributed in Central and South America. The three countries with the worst coffee production efficiency are Côte d'Ivoire (0.2482), Sierra Leone (0.2137), and Togo (0.1774), all located in Africa. In terms of coffee productivity, the average is 1.1318. Eleven countries are above the average and 28 countries are below the average. Among them, Guyana (0.9103), Yemen (0.8278), and Malawi (0.6275) have the worst coffee productivity. The study found that although coffee originated in Africa, the average coffee production efficiency of African countries (0.6167) lags behind non‐African countries (1.1563). However, the average coffee productivity of African countries (1.1766) is better than that of non‐African countries (1.1007). At present, coffee production efficiency in coffee‐producing countries in Africa is low, and technological improvements are being used to improve efficiency, making coffee productivity present an upward trend. This study chose to use the non‐oriented Super Directional Distance Model and Malmquist total factor productivity to evaluate the changes in coffee production efficiency and coffee productivity in African and non‐African countries. [EconLit Citations: D24, L22, Q10].